Effect of Combination between CaCl2 Dosage and Electric Stimulation Period on Meat Quality Duck Adult - Setyawardani, Triana; Wasito, Samsu (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2003)
Research entitled âThe effect of combination between CaCl2 dosage and length of electric stimulation on adult meat quality duck qualityâ. The aim was to know the effect of combination between CaCl2 and length of electric stimulation on quality. It was conducted at Technology of Animal Production Laboratory in Animal Science Faculty, Jenderal Soedirman University on June 2nd up to August 30rd 2002. Materials used in this research were 27 Tegal duck adult. Experimental design with Completely Randomized Design (CRD) with factorial 3 x 3 was performed in this research. The first factor was CaCl2 was dosage (a1=50cc; a2=100cc; and a3=150cc) and the second factor was length of electric stimulation period (b1=10 sec; b2=20 sec; and b3=30 sec). Each experiment was repeated three times, and variable of this research were pH, tenderness, WHC and CL. The result of research shows that CaCl2 dosage (50, 100, and 150 cc); length of electric stimulation and their interaction were gave no significant effect (P>0,05) on pH, tenderness, WHC and CL in adult duck meat. Conclusion of this research was CaCl2 dosage, electric stimulation period and their interaction gave the same effect on pH, tenderness, WHC and CL adult duck meat. (Animal Production 5(1): 25-34 (2003)Â Key word: Tenderness, WHC and CL, Duck, Meat, Electrical, Calsium Chlorida